1991
DOI: 10.1002/bjs.1800780923
|View full text |Cite
|
Sign up to set email alerts
|

Effect of initial biopsy procedure on prognosis in Stage 1 invasive cutaneous malignant melanoma: Review of 1086 patients

Abstract: After treatment for primary clinical Stage 1 invasive cutaneous malignant melanoma, 1086 patients were followed for a minimum of 5 years from initial operation. Patient data were retrieved from the unit's melanoma registry; 96 (8.8 per cent) were treated initially by incisional biopsy, 292 (26.9 per cent) by narrow margin excision biopsy and 698 (64.3 per cent) by wide margin excision. Logistic regression analysis was performed to assess the statistical significance of the association between the various facto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
60
0
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(62 citation statements)
references
References 18 publications
1
60
0
1
Order By: Relevance
“…13 Lees et al also indicated no significant averse effect of incisional biopsy in 96 patients, but 40% of the histopathological data was not assessable. 14 Austin et al did find a significantly reduced survival in the incisional biopsy group, but patients in the incisional biopsy group were also significantly older. 15 The two most recent publications found no negative influence of incisional biopsies on melanoma patient survival but in Bong et al patients groups were not fully matched and in Martin et al median FU was only 28 months.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…13 Lees et al also indicated no significant averse effect of incisional biopsy in 96 patients, but 40% of the histopathological data was not assessable. 14 Austin et al did find a significantly reduced survival in the incisional biopsy group, but patients in the incisional biopsy group were also significantly older. 15 The two most recent publications found no negative influence of incisional biopsies on melanoma patient survival but in Bong et al patients groups were not fully matched and in Martin et al median FU was only 28 months.…”
Section: Discussionmentioning
confidence: 92%
“…6 The influence of an incisional biopsy on melanoma patient survival has been discussed for many years and different investigators have found contradicting results. [7][8][9][10][11][12][13][14][15] Two recent publications concluding incisional biopsies not to interfere with melanoma patient survival were not able to end this discussion since patient groups were not fully comparable 16 or follow up (FU) was short. 17 This study investigated both the influence of diagnostic biopsy type and the presence of residual tumor cells in the re-excision specimen on melanoma patient disease free survival (DFS) and overall survival (OS), in 471 patients with a mean FU of more than 5 years.…”
mentioning
confidence: 99%
“…The outcome in patients diagnosed with melanoma is dependent, not only on tumour thickness, but also on the presence of regional or distant metastasis (Lees & Briggs, 1991). In fact, regional lymph node status is thought to be the most powerful prognostic indictor in clinically localized melanoma (Morton et al, 2006).…”
Section: Management Of the Regional Lymph Node Basinmentioning
confidence: 99%
“…Incisional biopsies may also render lesions difficult to assess on histopathological criteria, but they may be acceptable in certain anatomic locations such as the palm or sole, digit, face, ear, subungal areas, or in very large lesions. Incisional biopsies have not been associated with a worse prognosis, in terms of local or regional recurrence rates or mortality (Ledeerman & Sober, 1985;Lees & Briggs, 1991;Austin et al, 1996;Royal College of Surgeons, 2006).…”
mentioning
confidence: 99%
“…Apesar de haver evidências clínicas demonstrando que a biópsia incisional não prejudica a sobrevida 4,5 (B), é recomendável a biópsia excisional com margens pequenas, no sentido da obtenção de material adequado para avaliação anatomopatológica completa 6 (C). Na 1,3,21 (D).…”
Section: Recomendaçõesunclassified